PERBAIKAN SIFAT KIMIA TANAH FLUVENTIC EUTRUDEPTS PADA PERTANAMAN SEDAP MALAM DENGAN PEMBERIAN PUPUK KANDANG AYAM DAN PUPUK NPK - S, Mubarok; Kusumiyati1, Kusumiyati1; Zulkifli, A (Agrin, 2016)
Polianthes tuberosa L. is a potential flowering plant to be developed in Jatinangor, but, the type of soil inJatinangor belongs to Fluventic Eutrudepts has a lower of pH, medium of available K and potential K. Newstrategy is needed to resolve these problems such as by adding the organic and an-organic fertilizer. This researchwas conducted to determine the effect of the combination organic fertilizer and NPK on soil reaction (pH),available K, Potential K, and fresh weight of tuberose (Polyanthes tuberose L.) on Fluventic Eutrudepts. Theresearch design used was Randomized Block Design (RBD) with ten treatments and three replications, consist of:without organic fertilizer + NPK (control); without organic fertilizer + recommended dosage of NPK;recommended dosage of organic fertilizer + without NPK; ½ recommended dosage of organic fertilizer + ½recommended dosage of NPK; ½ recommended dosage of organic fetilizer + recommended dosage of NPK;recommended dosage of organic fetilizer + ½ recommended dosage of NPK; without organic fertilizer + 1 ½recommended dosage of NPK; 1 ½ recommended dosage of organic fertilizer + without NPK; 1 ½ recommendeddosage of organic fertilizer + ½ recommended dosage of NPK; 1 ½ recommended dosage of organic fertilizer +recommended dosage of NPK. The results show that there were effect of soil reaction (pH), available P, potentialP, and fresh weight of tuberose from combination of organic fetilizer and NPK. Treatments of 1 ½ recommendeddosage of organic fertilizer + without NPK gives the best results of 148,6 g plant-1 with an increase 63,2%compared with no treatment.Key words: fluventic eutrudepts, tuberose, chicken fertilizer, NPK fertilizer ABSTRAKSedap malam (Polianthes tuberosa L.) merupakan tanaman hias berbunga indah yang sangat potensialdikembangkam salah satunya di Jatinagor. Tanah di Jatinangor yang termasuk ke dalam sub group FluventicEutrudepts mempunyai reaksi tanah agak masam, K-potensial sedang, K-dd sedang, dan KTK rendah, sehinggaperlu dilakukan upaya untuk meningkatkannya yang salah satunya dengan pemupukan. Percobaan dilakukan untukmengetahui pengaruh pemberian kombinasi pupuk organik dan pupuk NPK terhadap K-potensial, K-dd, KTK danbobot segar tanaman sedap malam (Polyanthes tuberosa L.) pada Fluventic Eutrudepts. Rancangan percobaanyang digunakan adalah Rancangan Acak Kelompok (RAK) faktor tunggal dengan sepuluh perlakuan dan tigaulangan, yaitu terdiri dari : Tanpa pupuk organik + pupuk NPK (kontrol); Tanpa pupuk organik + dosis anjuranNPK; Dosis anjuran pupuk organik + tanpa pupuk NPK; ½ dosis anjuran pupuk organik + ½ dosis anjuran NPK;½ dosis anjuran pupuk organik + dosis anjuran NPK; Dosis anjuran pupuk organik + ½ dosis anjuran NPK; Tanpapupuk organik + 1 ½ dosis anjuran NPK; 1 ½ dosis anjuran pupuk organik + tanpa pupuk NPK; 1 ½ dosis anjuranpupuk organik + ½ dosis anjuran NPK; 1 ½ dosis anjuran pupuk organik + dosis anjuran NPK. Hasil penelitianmenunjukan terdapat pengaruh terhadap K-potensial, K-dd, KTK dan bobot segar tanaman sedap malam akibatpemberian kombinasi pupuk organik dan pupuk NPK. Perlakuan 1 ½ dosis anjuran pupuk organik + tanpa pupukNPK memberikan bobot segar tanaman sedap malam terbaik sebesar 148,6 g tanaman-1 dengan kenaikan bobotsegar 63,2% dibandingkan dengan tanpa perlakuan.Kata kunci: fluventic eutrudepts, sedap malam, pupuk kandang ayam, pupuk NPK